EXPERIMENTAL ANALYSIS OF ELECTRICAL CIRCUITS FROM ON-SITE AND REMOTELY CONTROLLED ACTIVITIES - Monteiro, Marco Aurelio Alvarenga [UNESP]; Germano, Jose Silverio Edmundo [UNESP]; Galvao, Idmaura Calderaro Martins (Univ Francisco Jose Caldas, Fac Science & Education, 2023)
In this work, we sought to compare the impact of carrying out experimental activities, in person and remotely controlled, on the learning of concepts related to electrical circuits by high school students in five public schools in the interior of Sao Paulo. In each school, two third-year classes were applied, one group submitted to the face-to-face experiment and the other to the remote experiment. The experiments addressed the concepts of association of resistors, electric current, electric voltage and dissipated electric power. Data were collected through questionnaires, pre-test and post-test, and analyzed using Cohen's D method (1977) and Gery's g factor (1972). Cohen's D method is a statistical measure used to assess the effect size (or magnitude of the difference) between two in-dependent samples, while Gery's g factor is a measure that compares the performance of groups in an experiment, taking into account the individual differences in ability or intelligence.The results indicated that carrying out the experiments played an important role in the students' learning, especially those who participated in the remotely contro-lled experiment. In addition to offering a contextualized approach to scientific concepts, remote experiments also provided students with the opportunity to manipulate real experiments at any place and time, becoming a promising activity method for Science Teaching. Therefore, the study suggests that the carrying out remote experiments can be an effective and safe way to promote the learning of scientific concepts by high school students, complementing face-to-face activities and allowing greater flexibility in carr-out activities.
Keywords: Physics Teaching; Remote controlled experiment; Electric circuits. Experi-mentation; Digital Information and Communication Technology